The diagnostic pitfalls of mucormycosis - Margherita Mauro; Giuliana Lo Cascio; Rita Balter; Ada Zaccaron; Elisa Bonetti; Virgina Vitale; Matteo Chinello; Massimiliano De Bortoli; Paolo Brazzarola; Costanza Bruno; Simone Cesaro (Mediterranean Journal of Hematology and Infectious Diseases)
Background Invasive mucormycosis is a very aggressive fungal disease among immunocompromised pediatric patients caused by saprophytic fungi that belong to the order of the Mucorales.